The effects of service quality, perceived value, satisfaction and trust on foreign patients' loyalty of medical tourism in Malaysia hospitals - Ahmad Ibrahim, Aljumah (Universiti Malaysia Perlis (UniMAP), 2018)
Doctor of Philosophy in Marketing